Hubungan Kebiasaan Mengorek Telinga Dengan Kejadian Otomikosis Pada Pasien di Poliklinik THT Rumah Sakit Budi Kemuliaan Kota Batam - Elvita Nora Susana; Isramilda Isramilda; Ike Nurjanah (Lembaga Pengembangan Kinerja Dosen, 2024)
Otomycosis is an ear infection caused by fungi, or a superficial fungal infection of the pinna and meatus auditorius - externus. The most common symptom is itching. Ear scraping causes disruption of the natural ear cleaning mechanism so that it is easy to develop otomycosis. Indonesia with a tropical climate has a high level of humidity causing fungal infections to occur easily in the human body, such as in the ear canal or called otomycosis. This study aims to determine the relationship between the habit of picking ears with the incidence of otomycosis in the ENT Polyclinic of Budi Kemuliaan Hospital, Batam kota in 2023. This study used an observational analytic design with a cross sectional design. The population in this study were all patients at the ENT Polyclinic of the Budi Kemuliaan Hospital, Batam Kota in 2023 with purposive sampling technique taking total sampling on a sample of 70 people. Data were analyzed using the chi square test. The results of this study obtained variables associated with the incidence of Otomycosis. Where with a frequency of >1x / week (often), 75% experienced otomycosis and ≤1x / week (rarely), 34.6% experienced otomycosis. There was a significant relationship between the frequency variable and the incidence of otomycosis (p value = 0.001). Based on the results of this study, it can be concluded that there is a relationship between the habit of scraping the ears with the incidence of otomycosis in patients of the ENT Polyclinic of Budi Kemuliaan Hospital, Batam Kota 2023.